2008
DOI: 10.4102/hsag.v13i1.257
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ experiences of labour in a tertiary care hospital

Abstract: The purpose of the study was to explore and describe experiences of mothers during childbirth in a tertiary hospital in the Limpopo Province. This was achieved through a qualitative research study which was exploratory, descriptive, contextual and inductive in nature. A sample of 24 mothers participated in this study. Data obtained from unstructured in-depth interviews were analysed according to the protocol by Tesch (1990, cited in Cresswell, 1994:155). Five themes were identified, namely mutual participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Women preferred healthcare providers that had kind attitudes, spent time with women, and were calm, tactful, warm, smiling, and caring . Women described their expectation to be treated as a person and not as ‘processed things’ . To be seen as an individual – with differences and peculiarities – was expressed by women and healthcare providers as being met with respect …”
Section: Resultsmentioning
confidence: 99%
“…Women preferred healthcare providers that had kind attitudes, spent time with women, and were calm, tactful, warm, smiling, and caring . Women described their expectation to be treated as a person and not as ‘processed things’ . To be seen as an individual – with differences and peculiarities – was expressed by women and healthcare providers as being met with respect …”
Section: Resultsmentioning
confidence: 99%
“…A study 'Experiences of childbirth by mothers at the tertiary hospital in Limpopo Province' was conducted (Maputle & Nolte 2008), and experiences of the mothers during childbirth revealed the major concept 'woman-centred care'. 'Womancentred care' emerged as a core concept because it was found to be the central idea or event, and all the other categories and attributes were contingent upon it.…”
Section: Methods: Concept Analysismentioning
confidence: 99%
“…Concept clarification is an important step in developing useful and usable knowledge in childbirth. In this article concept analysis was conducted subsequent to research undertaken in the tertiary academic hospital complex of the Capricorn district in Limpopo Province, that determined experiences of childbirth of mothers (Maputle & Nolte 2008) and their attending midwives (Maputle & Hiss 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although best practices for continuous support during childbirth are known, they are not generally implemented, either internationally (Bohren et al 2017) or in South Africa (Brown et al 2007;Maputle & Nolte 2008). According to Brown et al (2007), the level of care in South African is not ideal because most women do not benefit from the support of a childbirth companion.…”
Section: Introductionmentioning
confidence: 99%
“…According to Brown et al (2007), the level of care in South African is not ideal because most women do not benefit from the support of a childbirth companion. A South African study reported that mothers would prefer a childbirth companion, but were not informed about this possibility (Maputle & Nolte 2008).…”
Section: Introductionmentioning
confidence: 99%